The Relative Expression of Mig6 and EGFR Is Associated with Resistance to EGFR Kinase Inhibitors - Chang, Xiaofei (Public Library of Science, 2013)
The sensitivity of only a few tumors to anti-epidermal growth factor receptor EGFR tyrosine kinase inhibitors (TKIs) can be explained by the presence of EGFR tyrosine kinase (TK) domain mutations. In addition, such mutations were rarely found in tumor types other than lung, such as pancreatic and head and neck cancer. In this study we sought to elucidate mechanisms of resistance to EGFR-targeted therapies in tumors that do not harbor TK sensitizing mutations in order to identify markers capable of guiding the decision to incorporate these drugs into chemotherapeutic regimens. Here we show that EGFR activity was markedly decreased during the evolution of resistance to the EGFR tyrosine kinase inhibitor (TKI) erlotinib, with a concomitant increase of mitogen-inducible gene 6 (Mig6), a negative regulator of EGFR through the upregulation of the PI3K-AKT pathway. EGFR activity, which was more accurately predicted by the ratio of Mig6/EGFR, highly correlated with erlotinib sensitivity in panels of cancer cell lines of different tissue origins. Blinded testing and analysis in a prospectively followed cohort of lung cancer patients treated with gefitinib alone demonstrated higher response rates and a marked increased in progression free survival for patients with a low Mig6/EGFR ratio (approximately 100 days, P = 0.01).